The Use of Induced Pluripotent Stem Cells for the Study and Treatment of Liver Diseases. Issue 1 (1st February 2016) - Hansel, Marc C.; Davila, Julio C.; Vosough, Massoud; Gramignoli, Roberto; Skvorak, Kristen J.; Dorko, Kenneth; Marongiu, Fabio; Blake, William; Strom, Stephen C.
Abstract: Liver disease is a major global health concern. Liver cirrhosis is one of the leading causes of death in the world and currently the only therapeutic option for end‐stage liver disease (e.g., acute liver failure, cirrhosis, chronic hepatitis, cholestatic diseases, metabolic diseases, and malignant neoplasms) is orthotropic liver transplantation. Transplantation of hepatocytes has been proposed and used as an alternative to whole organ transplant to stabilize and prolong the lives of patients in some clinical cases. Although these experimental therapies have demonstrated promising and beneficial results, their routine use remains a challenge due to the shortage of donor livers available for cell isolation, variable quality of those tissues, the potential need for lifelong immunosuppression in the transplant recipient, and high costs. Therefore, new therapeutic strategies and more reliable clinical treatments are urgently needed. Recent and continuous technological advances in the development of stem cells suggest they may be beneficial in this respect. In this review, we summarize the history of stem cell and induced pluripotent stem cell (iPSC) technology in the context of hepatic differentiation and discuss the potential applications the technology may offer for human liver disease modeling and treatment. This includes developing safer drugs and cell‐based therapies to improve the outcomes of patients with currently incurable health illnesses. We also review promising advances in other disease areas to highlight how the stem cell technology could be applied to liver diseases in the future. © 2016 by John Wiley & Sons, Inc.